Use of 37% carbamide peroxide in the walking bleach technique: A case report - Teixeira, Érica Cappelletto Nogueira; Hara, Anderson Takeo; Serra, Mônica Campos (My University, 2004)
Dental bleaching represents an effective, conservative, and relatively low-cost method for improving the appearance of discolored pulpless teeth. Among the bleaching techniques, the walking bleach technique with sodium perborate associated with water or hydrogen peroxide stands out because of its esthetic results and safety. A modified walking bleach technique with the use of 37% carbamide peroxide as the bleaching agent is presented. Additionally, the adverse effects of dental bleaching in the following restorative procedures are discussed, showing the advantages with the use of 37% carbamide peroxide.
Keywords: Carbamide peroxide; Discolored tooth; Nonvital bleaching; Walking bleach; bleaching agent; unclassified drug; urea peroxide; adult; case report; clinical examination; clinical feature; dental care; endodontics; female; human; patient information; patient satisfaction; tooth color; tooth pulp disease; tooth radiography; tooth root canal; treatment outcome; Drug Combinations; Female; Humans; Middle Aged; Oxidants; Peroxides; Tooth Bleaching; Tooth Discoloration; Tooth, Nonvital; Urea